Prevalence of dissociative identity disorder among psychiatric outpatients in different cultural groups - May Mahmoud Abdellah; Khadiga Mohamed Ragheb; Taghreed Mohamed Elshafie; Rania Ahmed Hamed (Middle East Current Psychiatry)
Abstract Background Dissociative disorders (DDs) are characterized by a disturbance in the organization of identity, consciousness, perception, or memory. This disturbance involves disruptions of consciousness and limited access to information. One of the valuable updates in the recent study of DDs is the well-established link between dissociation and trauma. Dissociative identity disorder (DID) is the most widely discussed and recognized of the DDs. This work aimed to determine the prevalence and contributing factors of DID among psychiatric outpatients in two hospitals representing two different cultural groups located in Sohag and Cairo. Results According to the Structured Clinical Interview for DSM-IV Dissociative Disorders (SCID-D), the prevalence of DID patients is 4.8% and 6.8% according to DDIS, and the prevalence in Sohag versus Cairo is 5.3% versus 3.0% with no significant statistical difference. The prevalence of other dissociative disorders according to SCID-D in Sohag versus in Cairo is as follows: DDNOS 24 (8%) vs. 5 (5%), dissociative fugue 1 (0.3%) vs. 0 (0%), and depersonalization/derealization 6 (2%) vs. 1 (1%) with no significant statistical difference between the two studied groups. Conclusion The total prevalence of DID patients is 4.8 according to SCID-D and 6.8% according to DDIS, and the prevalence in Sohag versus Cairo is 5.3% versus 3.0% with no significant statistical difference, which means that DID is more prevalent in our psychiatric patients than usually mentioned and the use of specific diagnostic tools will benefit our management plans. These findings highlight the need for greater clinical awareness of dissociative disorders and DID among different psychiatric disorders.